ACTIVITY AND PRESSURE OF MAGNESIUM STEAM IN ALLOYS Ni-Mg-Si-Fe and Cu-Mg-Si-Fe - V. N. Vlasov; S. V. Buldygin; U. A. Ageev; V. I. Shkurkin (Литьë и металлургия)
The calculation of activity and pressure of magnesium vapour in melts Ni-Si-Mg-Fe and Cu-Si-Mg-Fe in metal systems at constant magnesium contents 6, 10, 14 и 18 mas.% and temperatures 1350 and 1450 °С is carried out in this work.